Recreação hospitalar: o papel do profissional de educação física na equipe multidisciplinar - Padovan, Diego; Schwartz, Gisele Maria [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
This qualitative study aimed to investigate the methodological perspective, the contents, possible outcomes and the role of Physical Education professionals in multidisciplinary staff of Recreation in hospitals. The study consisted of a survey applied to 20 adults of both sexes, volunteers, working in multidisciplinary team at a hospital in Leme, SP. Data were descriptively analyzed through content analysis technique, indicating that the time of engagement of that professional in that team was on average 12.8 months. Physical Education Professionals act mainly with joy faced the patients, making them well accepted. In relation to the contents used by these professionals, toys were the most mentioned, followed by books, puppets, role play and music. The team noticed some positive changes in patients after Physical Education Professional performances, and his engagement in the health team was considered very important, highlighting the urgency of new shares to enlarge this Professional participation in health multidisciplinary teams.

Este estudo qualitativo investigou as perspectivas metodológicas, os conteúdos, os possíveis resultados e o papel dos profissionais de Educação Física atuantes em equipes multidisciplinares com a recreação hospitalar. O estudo constou de pesquisa exploratória, do tipo survey, aplicada a 20 sujeitos adultos, voluntários, de ambos os sexos, atuantes em equipe multidisciplinar de um hospital em Leme, SP. Os dados analisados descritivamente, por Análise de Conteúdo Temático, indicam que o tempo de engajamento desse profissional nessa equipe foi, em média, 12,8 meses. O profissional de Educação Física age com alegria, frente aos pacientes, o que o torna bem aceito. Os conteúdos utilizados por esses profissionais nas intervenções foram brincadeiras, fantoches, dramatizações e música. A equipe percebeu alterações positivas nos pacientes, depois da atuação do Profissional de Educação Física, sendo seu papel considerado importante na equipe multidisciplinar. Sugerem-se novas ações para ampliar a participação deste profissional em equipes multidisciplinares de saúde.
Recreation in hospitals: the role of physical education professional in multidisciplinary attendance
Keywords: Health; Hospital; Recreation